Bioinformatics Identification of the Expression and Clinical Significance of E2F Family in Endometrial Cancer - Zhang, YunZheng; Wang, Zihao; Ma, Jian; Huo, JiaNing; Li, YiBing; Wang, YuShan; Chen, Hao; Shan, LuHe; Ma, Xiaoxin (Frontiers in Genetics, 2020)
Background: Besides being one of the most prevalent cancers among women, incidence and mortality rates of endometrial cancer (EC) are still increasing. E2F family of transcriptional factors is involved in cell differentiation, apoptosis and inhibition of DNA damage response, thus affects growth and invasion of tumor cells. Methods: We used multiple bioinformatics tools to explore the role of E2F family in endometrial cancer. Results: The expression of E2F1/2/3/7/8 was significantly up-regulated in endometrial cancer tissues, converse to E2F4 which was down regulated. Methylation down-regulates all E2Fs except for E2F2. Accordingly, E2F1/2/3/5/7/8 are potential diagnostic biomarkers for EC. In particular, EC patients displaying upregulated E2F1 and E2F3 expression had a worse overall survival and relapse-free survival. E2F8, E2F7 and E2F1 were the top three, most frequently altered genes in endometrial cancer. E2F family activates apoptosis pathways, regulates cell cycle and impairs DNA damage response pathways. Drug sensitivity analysis demonstrated that the level of E2F2/3/8 negatively correlated with drug resistance. Meanwhile, immune infiltrations analysis revealed that E2F family is associated with recruitment of several immune cells. Enrichment analysis on its part revealed that E2F family is mainly associated with cell cycle, sequence-specific DNA binding, nuclear transcription factor complex, PI3K-Akt signaling and p53 signaling pathway. We also identified multiple miRNA and kinase EF2 biomarker targets in endometrial cancer. Conclusion: Our study revealed the unique expression signature and clinical significance of E2F family in EC, demonstrating the potential clinical utility of these transcription factors (TF) in endometrial cancer.